Paleovegetation and Paleoclimatic Changes in the Yukon at 6 ka BP - Cwynar, Les; Spear, Ray (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTThe most recent paleoenvironmental change to affect the Yukon centres around 6.0 ka. In the forested southern Yukon, black spruce (Picea mariana) and green alder (Alnus crispa) expanded their populations at most sites between 6.5 and 6.0 ka. Even in the semi-arid region of SW Yukon these species increased their populations, although slightly later at 5.5 ka. These vegetation changes in the south imply cooler and wetter growing seasons, i.e. more mesic conditions. In the region of the upper Blackstone River of central Yukon, the modern vegetation consists of shrub tundra with scattered groves of white spruce (Picea glauca) and even fewer black spruce. Open forests of predominantly white spruce occupied the region as early as 9.5 ka, but between 6.5 and 6.0 ka white spruce declined as black spruce became the dominant tree, coincidentally with an increase in green alder. By 5.0 ka the vegetation had acquired its modern composition. As in the south, these changes imply cooling. Less evidence is available on the expansion of alder and black spruce in the northern Yukon. Both species increased in forested areas (forest-tundra) at 6.0 ka. These changes again imply cooling. Because both black spruce and green alder were present in Yukon well before 6 ka, these vegetation changes cannot be ascribed to migration lags.